1997
DOI: 10.1038/39369
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Smad7, a TGFβ-inducible antagonist of TGF-β signalling

Abstract: TGF-beta signals from the membrane to the nucleus through serine/threonine kinase receptors and their downstream effectors, termed SMAD proteins. The activated TGF-beta receptor induces phosphorylation of two such proteins, Smad2 and Smad3, which form hetero-oligomeric complex(es) with Smad4/DPC4 that translocate to the nucleus, where they then regulate transcriptional responses. However, the mechanisms by which the intracellular signals of TGF-beta are switched off are unclear. Here we report the identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
939
1
19

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,702 publications
(1,010 citation statements)
references
References 29 publications
27
939
1
19
Order By: Relevance
“…5 and Supplementary Table S4). In general, SMAD6 and SMAD7 play negative feedback loop in the TGF-β/SMAD signaling pathway and are considered as potential regulators of ovarian function (Nakao et al 1997, Uchida et al 2000, Tsukamoto et al 2014, Li 2015, while SMAD9 suppresses intracellular bone morphogenetic protein (BMP) signaling (Tsukamoto et al 2014). By decreasing the levels of these inhibitory SMADs, SMAD4-silencing might reduce inhibitory SMAD-related pathways or ovarian function in porcine follicular GCs.…”
Section: Discussionmentioning
confidence: 99%
“…5 and Supplementary Table S4). In general, SMAD6 and SMAD7 play negative feedback loop in the TGF-β/SMAD signaling pathway and are considered as potential regulators of ovarian function (Nakao et al 1997, Uchida et al 2000, Tsukamoto et al 2014, Li 2015, while SMAD9 suppresses intracellular bone morphogenetic protein (BMP) signaling (Tsukamoto et al 2014). By decreasing the levels of these inhibitory SMADs, SMAD4-silencing might reduce inhibitory SMAD-related pathways or ovarian function in porcine follicular GCs.…”
Section: Discussionmentioning
confidence: 99%
“…Once formed the complexes, the SMADs translocate in the nucleus where they regulate target genes (Attisano & Wrana 2000). In contrast, the inhibitory SMAD (I-SMAD), SMAD7, binds to TbRI and prevents the phosphorylation of R-SMADs, resulting in the inhibition of TGFb signaling (Imamura et al 1997, Nakao et al 1997. A SMAD ubiquitin regulatory factor 1 (SMURF1), being a HECTtype E3 ubiquitin ligase, interacts with I-SMAD7 and enhances the turnover of TbRI (Suzuki et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…SMAD7 is an inhibitory SMAD that antagonizes TGFb and BMP signaling in vitro (Nakao et al 1997, Yanagisawa et al 2001. SMAD7 is functionally distinct from SMAD6 (Yan et al 2009, Yan & Chen 2011.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that SMAD6 preferentially inhibits BMP signaling (Hata et al 1998, Ishisaki et al 1999, whereas SMAD7 is capable of targeting TGFb or both TGFb and BMP pathways (Nakao et al 1997, Souchelnytskyi et al 1998, Ishisaki et al 1999. The functions of inhibitory SMADs are being revealed by knockout mouse models.…”
Section: Introductionmentioning
confidence: 99%